Primary care for cancers at diagnosis and follow-up: a narrative review - Chew, Boon How; Taher, Sri Wahyu (Compuscript, 2013)
This paper is concerned about the family physician’s role in early cancer diagnosis and follow-up with his/hers patients who have just been diagnosed with cancer; treatment modalities for cancer; and family physician continuous roles for patients who are under definitive cancer treatment, experiencing side-effects of cancer treatment; some of the effective means to reduce these side-effects during cancer treatment and management of oncologic emergencies. Having some knowledge on the current cancer therapies would undoubtedly help family physicians to follow up patients with cancer more confidently, to appreciate their side-effects, symptomatic treatment, recognize the limit of primary care and be even useful for counseling and consultation with patients or their family members with a family history of cancer. Systematic searches with terms comprised “cancer”, “malignancy”, “primary care”, “general practice”, “cancer AND diagnosis” and “cancer AND follow-up” were done in the major databases such as Pubmed, ScienceDirect and Ovid. We employed selective searches with the above terms and their combination in some of the major journal such as The Lancet Oncology, The Lancet, New England Journal of Medicine, etc. These were followed by snowballing the relevant articles from the citation of references in those selected papers. The goal of this narrative review is not to provide exhaustive documentation of sound evidence for practice of primary care for cancer patients at diagnosis and follow-up. It mainly aims to provide specific evidence-based information and suggestions that are thought to be relevant for primary care professionals and policymakers.